Strategi Student Facilitator and Explaining (SFE) untuk Menumbuhkan Nilai-Nilai Karakter Peserta Didik - Rizal, Syaiful (Al-Riwayah : Jurnal Kependidikan, 2022)
Abstract : The purpose of Islamic religious education in general is to increase the faith, understanding, appreciation and experience of students about the religion of Islam. Character education itself is the character values ​​contained in the school curriculum. Meanwhile, the student facilitator and explaining (SFE) strategy is one of the learning strategies for how the teacher is able to present or demonstrate the material in the student's dapen and then give them the opportunity to explain it to their friends. The formulation of the problem in this study is how the student facilitator and explaining (SFE) strategy in growing the character values ​​of self-confidence, discipline and curiosity in class XI AK II students in Islamic religious education subjects. The research method uses a qualitative approach. The results showed that the strategy of student facilitator and explaining on the value of the character of self-confidence, discipline and curiosity seemed to have a significant impact.